Environmental monitoring of the state of environment of the Kumkol field. (Eurasian Journal of Ecology, 2016)
The condition of the main components of environment of the «Kumkol» field of the Ulytausky area of the Karaganda region located in the territory of the Republic of Kazakhstan is studied, at increasing anthropogenous process under the influence of a production activity of the person. Control supervision of pollution of atmospheric air by harmful substances on border of a sanitary protection zone of a field «Kumkol» recorded presence of carbon oxide, sulfur and nitrogen dioxides that was below sanitary indicators of maximum concentration limit. Water objects in the field territory generally an anthropogenous origin, in the chemical parameters and quality indicators correspond to household use. Hydrocarbons of an anthropogenous origin (an aliphatic row) are found in soils. The amount of oil products in soils doesn't exceed standardindicators.The radioactive background on districts and value of effective specific activity at stations doesn't exceed sanitary that is harmless for the working personnel.In model species of plants and animals of concentration of TM and NP are at the level of poorly polluted industrial territories.
Keywords: maximum permissible concentration; ecological assessment; nitrogen dioxide; carbon oxide; sulfur dioxide; hydrocarbons; heavy metals; oil products; radioactive background; air of a working zone; environmental monitoring; air pool